Ligation of the intersphincteric fistula tract for the treatment of fistula‐in‐ano: experience of a tertiary care centre in South India. (May 2016) - Parthasarathi, R.; Gomes, R. M.; Rajapandian, S.; Sathiamurthy, R.; Praveenraj, P.; Senthilnathan, P.; Palanivelu, C.
Abstract: Aim: Ligation of the intersphincteric fistula tract (LIFT) is a new sphincter‐sparing surgical technique increasingly used to treat fistulae‐in‐ano yielding good results. The aim of this study was to evaluate its effectiveness in the treatment of complex fistulae‐in‐ano and to determine factors associated with recurrence and its subsequent management. Method: A prospective observational study was performed of 167 patients with complex fistula‐in‐ano treated by LIFT from June 2013 to January 2014. In all patients a LIFT with partial core‐out of the fistula tract was performed. Results: There were 167 patients of mean age 43.6 ± 12.8 years. Thirty‐three fistulae were recurrent. 150 were trans‐sphincteric, 16 were intersphincteric and one was a suprasphincteric fistula. The median postoperative stay was 2 (range: 1–14) days (mean = 2.4 days). At follow up there was no change in continence. The median healing time was 4 (range: 1–8) weeks. Two patients developed an intersphincteric abscess needing surgical drainage healing uneventfully. The mean follow up was 12.8 [median = 12 (range: 4–22)] months. The healing rate was 94.1%. Ten (5.9%) patients developed a recurrent fistula that was managed by a second LIFT procedure in seven, a sinus tract excision with curettage in two and seton placement in one. Recurrence was significantly associated with diabetes mellitus and perianal collections and showed an increased incidence with tract abscesses and multiple tracts. Conclusion: LIFT has a high success rate in complex fistulae‐in‐ano. Recurrence is related to diabetes mellitus, perianal collections, tract abscesses and multiple tracts and a second LIFT procedure may be feasible and efficient.